Pain and disability in women with patellofemoral pain relate to kinesiophobia, but not to patellofemoral joint loading variables - De Oliveira Silva, Danilo [UNESP] (2020)
Background: Altered patellofemoral joint (PFJ) loading and elevated kinesiophobia are commonly reported in people with patellofemoral pain (PFP). However, the relative relationship of these physical-psychological variables with pain and disability in people with PFP is unknown. Aim: To explore the relationship of PFJ loading during stair ascent and kinesiophobia, with self-reported pain and disability in women with PFP. Methods: Fifty-seven women with PFP completed the Tampa Scale for Kinesiophobia, a Visual Analog Scale (0-100 mm) for pain during stair ascent, and the Anterior Knee Pain Scale (disability). Stair ascent mechanics were assessed via three-dimensional motion analysis while participants ascended an instrumented seven-step staircase. Peak PFJ contact force and stress, and PFJ contact force and stress loading rates were estimated using a musculoskeletal model. The relationships of PFJ kinetics during stair ascent and kinesiophobia, with the Anterior Knee Pain Scale (disability) and pain during stair ascent, were evaluated with Spearman rank correlation. Variables (kinetics and kinesiophobia) significantly correlating with the dependent variables (pain and disability) were inserted in linear regression models. Results: Kinesiophobia was moderately associated with self-reported pain (rho = 0.37) and disability (rho = −0.58) in women with PFP. No PFJ loading variables were found to be associated with self-reported pain or disability (P >.05). Kinesiophobia explained 14% of the variance of participants’ pain while ascending stairs and 33% of the variance of participant's self-reported disability. Conclusion: Addressing kinesiophobia during treatment of women with PFP may be important to reduce self-reported pain and disability.